Is There a Link Between Coffee Aroma and the Level of Furanmethanethiol (FMT) in Pinotage Wines - Garrido-Bañuelos, G.; Buica, A. (South African Journal of Enology and Viticulture, 2020)
Over the years, Pinotage has found its way into the South African and international market. Producers have used the flavour potential of this “original” South African grape to produce different wine styles, one of them being the so-called “coffee-style Pinotage”. The current study aims to explain the impact of furanmethanethiol (FMT) on the characteristic coffee aroma of these coffee-style wines. Chemical and sensory evaluation, as well as data mining of the technical information available, was performed. Not all wines marketed as “coffee Pinotage” showed a high “coffee” rating. However, the results showed a good correlation between the aroma perception and FMT concentrations (R2 = 0.81). However, RV coefficients were low when comparing the coffee rating with the information provided on both the front and the back label, which shows that, in some cases, the use of the “coffee Pinotage” term was rather part of the marketing strategy.